GEOTRAIL PLANNING OF GEOTOURISM AREA CIMENYAN SUB-DISTRICT, BANDUNG REGENCY - Ersalora Lutfianti (Centre For Tourism Planning and Development, 2017)
Bandung Regency has characteristic of tourism products which are dominated by mountains, crater, lake, and plantation. Special treatment is required, because of some area is a conservation area, one of which is a geological site the Lembang Fault. This article is using mix method approach between qualitative and quantitative. Qualitative approach is used to describe the supply and spatial analysis. Spatial analysis helps to analyse the topography of the area, land use, and prone of land movement areas. Thereafter, the result is synthesized by using ArcGIS 10.2 software to find out the most suitable and not in the study area, to determine the zonation planning. Meanwhile, quantitative approach is used for demand analysis by processing the visitor questionnaires data.